Physiological effect of exercise - Robertson, Blanche (My University, 1908)
Introduction: When speaking of the effect of exercise to the human body, a new meaning is given to the word “exercise.” The occasional morning walk or ride, a day’s rample in the woods, or a gymnasium lessen taken once or twice a month, it is not what is meant by exercise, but something, whatever it may be, that is done again and again, perhaps for pleasure only, but with the additional idea of perfecting ourselves in practice.
Citation: Robertson, Blanche. Physiological effect of exercise. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Exercise; Physiology; Muscles; Graduating theses; Senior theses; Theses